Education and citizenship: the need to open up spaces for dissent and dialogue (Foro de Educacion, 2016)
This brief paper highlights the importance of education for citizenship while raises the need to revise its sense in light of new demands and challenges, both social and political. But it also draws attention to the limits of any education system seen as a direct solution to them. With this contribution the monographic “Citizenship Education: meaning and experiences “ is presented. This is a special issue that in its first part presents some analysis and theoretical reflections that help to understand what should or can be expected of a civic education. The following are two articles analyze the initial teacher training on citizenship education in different educational levels. Finally, an overview of some lines and research contexts about citizenship education and practical experiences related to the topic both inside and outside of schools is offered.